Perilaku Penggunaan Alat Pelindung Diri pada Buruh Perempuan di Pabrik Pengupasan Udang - Balqisthi Ega Wanda; Susilawati Susilawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Female workers at the shrimp peeling factory work in a cold room and are given the implementation of occupational health and safety (K3), which is an effort made to protect workers who are good and healthy against risks that may arise as a result of work. When working at the shrimp peeling factory, you are always required to use personal protective equipment (PPE). Personal Protective Equipment (PPE) is the main concern of K3 equipment which is used to protect all or part of the body when working. Personal Protective Equipment (PPE) is very important for women's protection in the short and long term. Some of the personal protective equipment used by female workers in shrimp peeling factories are masks, hair caps, aprons, boots and latex gloves. Usually these latex gloves are rarely used by workers because they are slippery, hinder the speed of work, and are uncomfortable because of the water. getting into gloves means that wearing gloves is often neglected and some female workers experience irritation on the skin of their palms. The aim of this research is to determine the habits of female workers' use of personal protective equipment and the consequences of frequently neglecting to wear personal protective equipment. Research Methods carried out a correlational analysis method with a cross-sectional approach with a sample size of 20 respondents. In conclusion, female workers are always provided with protective equipment to work in peeling and cleaning shrimp, but because the work system is piecework, workers choose fast work because they feel they are experienced and professional enough, they rarely use gloves because they are slippery and uncomfortable. This is what causes some workers to experience irritation on the skin of their palms.